The Role of Religion-based Communication in Environmental Revitalization and Community Empowerment in Wonosobo - Raden Roro Ilma Kusuma Wardani (Prospect Publishing, 2022)
Forests in Wonosobo Regency play a role in maintaining ecological balance. The problem that often occurs is the decline in forest function. Various human activities are carried out to change the ecological function of forests into economic land use. One of the environmental conservation efforts is through religious character education. This was done by one of the opinion leaders in Tambi Village, Kejajar District, Wonosobo Regency. The purpose of this paper is to discuss the role of religious communication in efforts to revitalize the environment in a community empowerment process. This study uses a descriptive qualitative method with a character study approach. As a mission to revitalize the environment, an agent of change takes an approach with a religious context. This process was carried out using a pilot model method by the opinion leader Mr. RM, which started in a small community, namely the Agro Mulyo group. Starting from social change based on Islamic values. The role of religious communication in environmental revitalization in community empowerment: 1) communication as a medium of da'wah; and 2) communication as the basis for friendly interaction (strengthening ukhuwah). The principles of religious communication are: 1) oriented towards the physical and spiritual well-being of the community; and 2) religion-based empowerment is an effort to do social engineering. This paper concludes that religious communication can save itself and its citizens from environmental damage to achieve a balanced happiness between the world and the hereafter.